Are temporary work agencies stepping stones into regular employment? - Joakim Hveem (IZA Journal of Migration, 2013)
This paper estimates the causal effect of temporary work agency (TWA) employment on the subsequent probability of employment in the regular labor market. The main purpose is to estimate the stepping-stone effect separately for natives and immigrants, where the latter group potentially benefits the most from TWA employment. Since no quasi-experiment is available, individual Differences-in-Differences and matching is used to deal with the potential selection bias. The results point at a negative regular employment effect, which slowly fades away over a couple of years. Thus no evidence of a stepping-stone effect is found. When conditioning on immigrants, this negative effect is absent. A long-run significant effect is found on overall employment probability (including TWA employment), there is even a long-run positive effect on annual earnings (mainly driven by women). Unemployment probabilities decreased, however the results in the estimation were less stable over time compared to the employment estimates, suggesting that the TWAs might keep individuals from exiting the labor market.
Keywords: 330; Temporary work agencies; Stepping stone; Labor market; Matching